Temperature and Humidity Control System for 20 kV of Cubicle with Multiple Input Multiple Output Fuzzy Logic Controller - Ramadhan, Mochammad Berliano Putra; Efendi, Moh. Zaenal; Nugraha, Syechu Dwitya (JAREE (Journal on Advanced Research in Electrical Engineering), 2023)
Cubicle 20 kV is a crucial electrical equipment in the 20 kV power distribution system. Often, cubicle issues arise due to excessively low or high temperatures and humidity, which can lead to the presence of water spots and corrosion on the components inside the 20 kV cubicle. One of the efforts to maintain the reliability of this 20 kV cubicle is to ensure that the temperature and humidity inside the cubicle remain within their operational limits. To achieve this, a system is needed to control the temperature and humidity in the 20 kV cubicle. The system can monitor and control the temperature and humidity inside the cubicle by adjusting the activation angle of the exhaust fan and heater. Control is achieved using a multiple-input, multiple-output fuzzy logic controller. The main components of this system are the STM32 microcontroller, DHT22 sensor, and ESP8266 module for monitoring temperature and humidity via a website. System has successfully controlled temperature and humidity d with a set point value of 35 °C and humidity of  60% RH. This implementation of fuzzy multiple input multiple outputs has performed well and resulted in only a small error of 0.55% for temperature and 1.05% for humidity.With the presence of this device, the temperature and humidity in the cubicle 20 kV can be controlled, and it enables the PLN operator to easily monitor and maintain the cubicle 20 kV.